Terminology of Democracy in the Quran On the Dimensions of Constitutional Law - Rohmah, Siti Ngainnur; Yunus, Nur Rohim (BULETIN ADALAH, 2024)
This essay examines the terminology of democracy as mentioned in the Quran and evaluates its significance within the framework of contemporary constitutional law. While the term "democracy" is not directly stated in the Quran, essential democratic elements can be recognised in terms such as discussion (shura), fairness ('adl), and public welfare (maslahah). The objective of the debate is to explore the applicability of the democratic rhetoric found in the Koran within the framework of contemporary constitutional legislation. Furthermore, it is vital to analyse the ramifications of these principles on policy development, governmental procedures, and community engagement in the political sphere. By examining the verses of the Quran that pertain to contemplation, fairness, and the well-being of society, it may be inferred that these ideas hold great importance in establishing a democratic and inclusive governmental framework. The incorporation of democratic language in the Koran can offer moral and ethical direction to policymakers in guaranteeing the engaged involvement of citizens and the safeguarding of their rights in contemporary constitutional legislation.